My ex, the antichrist - DiLouie, Craig, 1967- (Run For It, 2025)
"1998: A punk band is formed by Lily Lawlor and Drake Morgan. Drake inspires faith in some. Fear in others. Lily is a believer. 1999: A Battle of the Bands ends in a shocking death, and a riot that claims the lives of three teenagers. 2009: At the height of her stardom, Lily walks into a police station and confesses to murder. Now: The band has refused to talk to the press about the night of the riot, Lily's confession, or anything else. It's been over a decade, but Lily has finally agreed to an interview. And the band is following her lead. What follows is a story of prophecy, death, and apocalypse. A story about love and love lost. A story about the antichrist. Maybe it's all true. Maybe none if it is. Either way, this is their story. And they're sticking to it"--